2015
DOI: 10.1007/s10549-015-3643-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between progression-free survival and overall survival in metastatic breast cancer patients receiving anthracyclines, taxanes, or targeted therapies: a trial-level meta-analysis

Abstract: Over the past decade, several new drugs have received regulatory approval for metastatic breast cancer (MBC). However, some of these approvals were based on improvement in progression-free survival (PFS), without a concomitant increase in overall survival (OS). This has led some to question the utility of using PFS as a measure for drug approval. To address the uncertainty of using PFS as a surrogate for OS in MBC, a systematic literature review followed by a trial-level correlative analysis was conducted in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 22 publications
1
34
0
3
Order By: Relevance
“…Overall, our results are highly consistent with the results of the two pivotal randomized studies of EM in MBC, reporting a significant and meaningful impact on OS and marginal impact on PFS, and no significant difference in the early therapeutic lines. These results are surprising, as it is generally assumed that PFS could be used as a surrogate endpoint for OS, but that a significant increase in PFS is required to increase OS. Nevertheless, our results, that is, a modest effect on PFS and a greater impact on OS, are extremely consistent with all previously reported comparative data of EM use in MBC .…”
Section: Discussionmentioning
confidence: 96%
“…Overall, our results are highly consistent with the results of the two pivotal randomized studies of EM in MBC, reporting a significant and meaningful impact on OS and marginal impact on PFS, and no significant difference in the early therapeutic lines. These results are surprising, as it is generally assumed that PFS could be used as a surrogate endpoint for OS, but that a significant increase in PFS is required to increase OS. Nevertheless, our results, that is, a modest effect on PFS and a greater impact on OS, are extremely consistent with all previously reported comparative data of EM use in MBC .…”
Section: Discussionmentioning
confidence: 96%
“…An FDA‐sponsored meta‐analysis of more than 12,000 patients receiving therapy in randomized clinical trials for lung cancer performed between 2003 and 2014 found no clear association between PFS and OS . Associations between PFS and OS in recent trials of patients with advanced breast cancer or ovarian cancer have also been inconsistent .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several novel therapies have been approved for use in patients with advanced NET based on their ability to slow tumor progression. The mammalian target of rapamycin (mTOR) inhibitor everolimus and the tyrosine kinase inhibitor sunitinib both improve PFS in pancreatic NET; everolimus was also recently confirmed to improve PFS in nonpancreatic NET . Although these randomized studies clearly demonstrated improvements in PFS, they did not show clear improvements in OS, although the number of deaths in these studies was relatively low at the time of data analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Modern cancer therapies for breast cancer include chemoterapeutic, anti-hormonal and molecular agents [ 6 9 ]. Different classes of chemoterapic agents are currently approved for treatment of metastatic BC: antracylines, anti-mitotic agents (including taxanes, vinorelbine, eribulin), alkylating agents (such as cisplatin and carboplatin) and anti-metabolites (5-fluorouracile, capecitabine, and gemcitabine) [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%